2008
DOI: 10.1590/s0004-27492008000500006
|View full text |Cite
|
Sign up to set email alerts
|

Ação do colírio de fenilefrina 10% no posicionamento palpebral de indivíduos normais

Abstract: Ação do colírio de fenilefrina 10% no posicionamento palpebral de indivíduos normaisDescritores: Pálpebras/fisiologia; Pupila; Fenilefrina/administração & dosagem; Fenilefrina/ farmacologia; Soluções oftálmicas Objetivos: Determinar a ação de uma gota do colírio de fenilefrina 10% sobre as pálpebras superior e inferior de indivíduos normais; verificar a ocorrência de alterações no posicionamento das pálpebras superior e inferior do olho contralateral, após instilação desta medicação. Métodos: Estudo prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
3
2
1
Order By: Relevance
“…We found a small, although highly significant difference in PFH between the treated eye and the untreated eye (∆PFH), in accordance with the measures reported by Bastiaensen et al 6 in a cohort of patients with insulin-dependent diabetes. The ∆PFH response in healthy particpants 3 5 is up to 70% higher in comparison with our measures, indicating a loss of sympathetic reserve capacity caused by decreased adrenergic excitability and autonomic dysfunction .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We found a small, although highly significant difference in PFH between the treated eye and the untreated eye (∆PFH), in accordance with the measures reported by Bastiaensen et al 6 in a cohort of patients with insulin-dependent diabetes. The ∆PFH response in healthy particpants 3 5 is up to 70% higher in comparison with our measures, indicating a loss of sympathetic reserve capacity caused by decreased adrenergic excitability and autonomic dysfunction .…”
Section: Discussioncontrasting
confidence: 70%
“…Consequently, topical application of phenylephrine, a sympathomimetic drug, causes an increase in palpebral fissure height (PFH) in healthy subjects of 1.2 to 1.6 mm accordingly. 3 5 In diabetes, however, the PFH is significantly decreased compared with healthy controls. On average, people with diabetes who depend on insulin had a PFH of 8.3 mm, whereas healthy controls had a PFH of 9.9.…”
mentioning
confidence: 98%
“…Entretanto, para que os dados possam ser validados há necessidade de se ter critérios bem definidos de inclusão e exclusão dos participantes, devendo-se levar em conta que os indivíduos que utilizam colírios podem ter alterações na fenda palpebral decorrente da ação dos mesmos nos músculos palpebrais, como ocorre, por exemplo, com o colírio de fenilefrina (13) . Ainda, a técnica de tomada das imagens deve ser sempre a mesma, já que a DMR e a fenda palpebral se alteram de acordo com a posição do olhar (14) .…”
Section: Discussionunclassified
“…Phenylephrine is a sympathomimetic drug commonly used topically in ophthalmology to induce dilatation of the pupil, allowing for examination of the In addition to stimulating the iris dilator muscle, phenylephrine also stimulates the sympathetically innervated superior and inferior tarsal muscle 111 , by activating α-and β-receptors 112 , resulting in increased palpebral fissure height (PFH) [113][114][115] . Thus, phenylephrine can be used to assess the suitability of Müllers muscle-conjunctival resection surgery in patients with mild to moderate upper eyelid ptosis 116 .…”
Section: Pharmacologic and Physiologic Modulation Of The Autonomic Ne...mentioning
confidence: 99%
“…In healthy individuals, one study found the average PFH to be 9.9 mm 212 , and phenylephrine has been shown cause increases in PFH between 1.2-1.6 mm [113][114][115] . In insulin-dependent diabetes, the average PFH was 8.3 mm, and the decrease was associated with the disease duration and severity of DR 212 .…”
Section: Assessing Palpebral Fissure Heightmentioning
confidence: 99%